Creating dynamic schools through mentoring, coaching, and collaboration - Carr, Judy F. ; Herman, Nancy, 1950- ; Harris, Douglas E. (Association for Supervision and Curriculum Development, 2020)
Building professional relationships -- Mentoring new teachers -- Organizing study groups -- Coaching -- Leading and supporting collaboration -- Building and sustaining learning communitiies.